Serotyping of Pasteurella multocida isolated from swine lungs collected at slaughter. - Pijoan, C (1983)
We serotyped 222 Pasteurella multocida strains isolated from swine lungs at slaughter. Capsular serotypes A and D were determined by the hyaluronidase sensitivity and acriflavin agglutination tests, respectively. Somatic antigens were determined by gel diffusion against standard antisera. Capsular serotype A was found in 97.3% of the strains and serotype D in the remaining 2.7%. The primary somatic antigen most commonly found was type 3 (86.0%). Type 5 was also very common (88.7%), but was usually a secondary antigen. The most common overall serotype was A:3(5) (39.2%). Other common serotypes were: A:3(4,5,12) (12.2%); A:3(4,5) (11.2%); A:3(5,12) (10.4%); A:3 (6.8%); and A:5 (6.8%). Type D strains had a similar distribution of serotypes, but with a higher prevalence of D:5 (33.3%) and D:3(5) (33.3%).